BRANDING OF RADIO SUARA KOTA MATARAM THROUGH THE PROGRAM "REGIONAL DEVICE ORGANIZATION (OPD) GREETING" IN MAINTAINING EXISTENCE IN THE DIGITAL ERA - Gemuh Surya Wahyudi; Silviya Hartati (TASAMUH, 2024)
Radio Suara Kota is a radio managed by the Mataram city government which is currently experiencing a decrease in the number of listeners, due to changes in the use of social media by the public, one of its flagship programs is the "Regional Apparatus Organization (OPD) Menyapa" program, Suara Kota needs to do branding so that the radio can be recognised by the public and build an image in the eyes of the public as a radio that connects the public with the government regarding the policies of the Mataram city government. This research method uses descriptive qualitative with the research subject, namely the "Regional Apparatus Organization (OPD) Menyapa" program. Data collection methods using interviews, observation and documentation. The results of this study are brand positioning, namely radio positioning itself to be the center of Mataram city government information to the public. Brand Identity is the radio has identity, one of which is the tagline "radio Suara Kota Suara Kita" and has unique program names such as MAHAR Mataram Harum and OPD Menyapa.